Influence of Ageing and Regional Differences on Draught Performance of Umblachery Cattle - M, Kousalya Devi; SMK, Karthickeyan; R, Venkataramanan; SN, Sivaselvam; KG, Tirumurugaan (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
An attempt was made to assess the effects of aging, regional differences, and draught load applied on draught potential of Umblachery cattle, an important draught breed of South India. Age had a highly significant effect (p <0.01) on all morphometric traits, stride length, and significant effect (p <0.05) on pulse rate after work. The middle age group (5.0–7.5 years) with more substantial stride length was identified as the critical productive age group for draught ability. Regional differences had a highly significant (p <0.01) influence on stride length, horsepower, and a significant effect (p <0.05) on pulse rate after work. The optimum draught load with which Umblachery breed could give uniform and maximum power output was found to be around 75 to 78 kg.